The Influence of the Effectiveness of Implementing Accounting Information Systems, Utilization of Technology, Human Resource Competency and Management Participation on Individual Performance: Study at Shopee Express Delivery Service Companies in Medan City - Ryo Eru Nugraha Ginting; Herlin Munthe; Merry Rusida S; Kiki Hardiansyah Siregar (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2023)
The objective of this study is to investigate the impact of the implementation of accounting information systems, technology use, human resource competency, and management engagement on individual performance at Shopee Express, a delivery service firm located in the city of Medan. The present study employs quantitative data. The research was carried out at a logistics company called Shopee Express, located in the urban area of Medan. The study's population comprises all employees employed at the Shopee Express delivery service company in the city of Medan, amounting to a total of 60 individuals. The sample size for this study also consists of 60 people. The study incorporated a combination of primary and secondary data sources, as employed by the researcher. The findings and analysis of this study are presented as follows: (1) The implementation of accounting information systems has a noteworthy impact on individual performance, as evidenced by the statistical significance of the sig value being less than 0.05. The impact of technology utilization on individual performance is shown to be statistically significant, as indicated by a significance level of less than 0.05. The competency of human resources has a substantial impact on individual performance, as indicated by a statistically significant p-value of less than 0.05. The involvement of management has a substantial impact on the performance of individuals, as evidenced by the statistical significance of the relationship (p < 0.05). (5) The concurrent impact of establishing accounting information systems, utilizing technology, possessing human resource competence, and engaging in management participation has a noteworthy effect on individual performance, as indicated by a statistically significant p-value of less than 0.05. The Adjusted R-Square value is 0.641, indicating that the research variables provide a substantial contribution of 64.10% towards explaining individual performance. The remaining 35.90% is attributed to external factors beyond the scope of this study.